High Rate of Turnover Intention: Study of Logistics Industrial Workers - Mohammad Annas; Tessa Handra (Pandawan Sejahtera Indonesia, 2023)
The research aims to uncover the root cause of the high rate in terms of logistic employee turn-over at the top ten logistics establishments under the management of Kawasan Berikat Nusantara located at the busiest logistics hub in the northern part of Indonesia. Ninety-eight respondents who were all decision makers representing ten major logistics establishments gave the primary data through structured questionnaires. Regression analysis was used to analyze the collected data as well as the description of hypothesis results. The conclusion showed that although the high tension of heavy industry in particular the logistics sector caused high job stress; it was not affecting the turn over intention of the employee. On the other side, employee job satisfaction gave more impact on employee turn-over. This circumstance gave a clear and objective description that job stress was really only the perception of the employee where they have their own flexibility and got full understanding related to the individual stress aspect. It concluded that logistics sector employees could tolerate job stress much better than their job satisfaction.